Efficacy of Bisphosphonate-Conjugated Sitafloxacin in a Murine Model of S. aureus Osteomyelitis: Evidence of “Target & Release” Kinetics and Killing of Bacteria Within Canaliculi - Ren, Youliang; Xue, Thomas; Rainbolt, Joshua; Bentley, Karen L. de Mesy; Galloway, Chad A.; Liu, Yuting; Cherian, Philip; Neighbors, Jeffrey; Hofstee, Marloes I.; Ebetino, Frank H.; Moriarty, Thomas Fintan; Sun, Shuting; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
S. aureus infection of bone is incurable due to its ability to colonize the osteocyte-lacuno canalicular network (OLCN), rendering it resistant to standard of care (SOC) antibiotics. To overcome this, we proposed bone-targeted bisphosphonate-conjugated antibiotics (BCA). Initial studies demonstrated that bisphosphonate-conjugated sitafloxacin (BCS) and hydroxybisphosphonate-conjugate sitafloxacin (HBCS) kills S. aureus in vitro. Here we demonstrate the in vivo efficacy of BCS and HBCS versus bisphosphonate, sitafloxacin and vancomycin in a murine model of implant-associated osteomyelitis. Longitudinal bioluminescent imaging (BLI) confirmed the hypothesized “target and release” kinetics of BCS and HBCS. Micro-CT of the infected tibiae demonstrated that HBCS significantly inhibited peri-implant osteolysis versus placebo and free sitafloxacin (p<0.05), which was not seen with the corresponding nonantibiotic-conjugated bisphosphonate control (HPHBP). TRAP-stained histology confirmed that HBCS significantly reduced peri-implant osteoclast numbers versus placebo and free sitafloxacin controls (p<0.05). To confirm S. aureus killing, we compared the morphology of S. aureus autolysis within in vitro biofilm and infected tibiae via transmission electron microscopy (TEM). Live bacteria in vitro and in vivo presented as dense cocci 1m in diameter. In vitro evidence of autolysis present as remnant cell walls of dead bacteria or “ghosts” and degenerating (non-dense) bacteria. These features of autolyzed bacteria were also present among the colonizing S. aureus within OLCN of infected tibiae from placebo, vancomycin and sitafloxacin treated mice, similar to placebo. However, most of the bacteria within OLCN of infected tibiae from BCA treated mice were less dense and contained small vacuoles and holes >100nm. Histomorphometry of the bacteria within the OLCN demonstrated that BCA significantly increased their diameter versus placebo and free antibiotic controls (p>0.05). As these abnormal features are consistent with antibiotic-induced vacuolization, bacteria swelling and necrotic phenotype, we interpret these findings to be the initial evidence of BCA-induced killing of S. aureus within the OLCN of infected bone. Collectively, these results support the bone targeting strategy of BCA to overcome the biodistribution limits of SOC antibiotics and warrant future studies to confirm the novel TEM phenotypes of bacteria within OLCN of S. aureus infected bone of animals treated with BCS and HBCS.